The European Small Business Finance Outlook 2023 - Helmut Krämer-Eis; Antonia Botsari; Salome Gvetadze; Frank Lang; Wouter Torfs (European Investment Fund (EIF), 2023)
This working paper provides an overview of the main markets relevant to the EIF, thereby documenting the impact of the polycrisis and the related challenging economic environment on SME financing. The publication first discusses the general market environment and then covers the markets for SME equity and debt products. In addition, it focuses on a number of thematic policy areas that are of particular interest to the EIF, such as Inclusive Finance, Fintech and Green finance & investment.
Keywords: 330